The Camisea Gas - Guerra, Daniel (2001)
On 9 December 2000, the license agreement for the exploitation of the Camisea gas between the Peruvian government and the consortium of companies Pluspetrol Peru Corporation, Hunt Oil USA, Korea and hydrocarbons SK Andean of Argentina was signed. ....